Two-Stage Optimal Configuration of Microgrid Based on Fuzzy Scene Clustering - MI Yang, LI Haipeng, CHEN Boyang, PENG Jianwei, WEI Wei, YAO Yan (Shanghai Jiaotong Daxue xuebao, 2023)
Aimed at the impact of extreme weather on the stable operation of microgrid, an optimal configuration strategy of microgrid based on fuzzy scene clustering is proposed. Using historical weather data, a fuzzy scene clustering method is used to deal with the problem of new energy output fluctuations caused by random weather on the source side, and a robust optimization model is established on the load side to deal with load fluctuations within a certain range. Using scenes of 8 760 hours in a year, typical scenes and extreme scenes are obtained by distinguishing the unique membership characteristics of fuzzy scene clusters. Considering the impact of extreme scenarios on the optimal configuration of the microgrid, a two-stage robust model with the smallest comprehensive cost is established, which is decomposed by the column and constraint method, and is finally solved iteratively by Cplex solver. The effectiveness and feasibility of the proposed optimal configuration strategy are verified by simulation analysis.